Higher education at the crossroads of disruption : the university of the 21st century - Kaplan, Andreas (Great debates in higher education., 2021)
The digital transformation of higher education has the same reputation as the higher education sector itself: rigid and reluctant to change. Covid- 19 has radically changed this rigidity, with thousands of Universities compelled to go 100 percent online in just a few days. Threatened by edtech start- ups, big tech corporations increasingly interested in academia, as well as venture capitalists attracted by the sector's high profit margins, Universities need to change their way of doing business to stay in business. Higher Education at the Crossroads of Disruption: The University of the 21st Century looks at the various areas of higher education that will likely undergo radical changes. Learning and teaching approaches will increasingly move into the digital sphere; advances in artificial intelligence as well as (big) data availability, will change the way academia works. This books examines how teaching formats will vary, and how curricula and course content will evolve. Higher education will most likely focus on skills development, with a stronger emphasis on inter- and multidisciplinary study content, and a steady turn toward society's well- being and sustainability. This is essential reading for those holding a leadership position in higher education, researchers with a focus on higher education, and to anyone interested in the evolution and future of higher education.